Pengaruh Knowledge Manajemen Dan Stabilisasi Ekonomi Terhadap Keberlanjutan Usaha (Studi Empiris Pada Balkondes Di Borobudur) - Shofiyani, Dianah; Hana, Marisa Tri; Nugraheni, Nur Aisah; Candra, Septian Dwi; Nurfadhilah, Ilfi; Muhdiyanto (Universitas Muhammadiyah Metro, 2024)
An organization or business will experience sustainability depending on the conditions andstrategies implemented and management of the business. This research aims to find out theinfluence of management knowledge on business sustainability, knowing the influence ofeconomic stabilization on business sustainability. This research uses quantitative methods.The population of this study were Balcondes and BUMDes managers in 20 Balcondes inBorobudur. The sample in this study was 165 respondents using a purposive samplingmethod. The analytical tool used is multiple linear regression with the help of SPSS 25. Theresults of this research show that knowledge management has a positive effect on businesssustainability, economic stabilization has a positive effect on business sustainability.